Desarrollo de un simulador para un gobernador de plantas hodroeléctricas en LabView para la instrucción de operadores - Bianchini-Obando, Luis Diego (Instituto Tecnológico de Costa Rica, 2002)
The feature work It’s being realized by a last level student from the Technological Institute of Costa Rica, in the Research and development center of the National Institute of electricity (ICE). Its main objective it’s to simulate a governor for a hydro electric plant based on LabView for the instruction of operators. As part of the methodology, it was made a flux diagram which describes the control logic of the governor; in order to this, it was selected the mathematical model for a Francis turbine, validated on Matlab by the ICE to be taken as base for the design of the program on LabView for the governor. Finally it was created a software package for a PLC Modicom, which serve as an external interface of variables of interest for the governor. The main conclusion obtained from this project was to emphasize the Lab View, as a powerful a versatile tool on engineering applications, as well of the efficiency of their specialized packages for the simulations of processes on real time. This project is the first part for the design of hydro electrical power plants that it’s on development by the Research and development center of the National Institute of electricity.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2002.
Keywords: Distribución de energía eléctrica; Flujo de datos; Electricidad; Software; Hardware